2020
DOI: 10.3390/insects11060349
|View full text |Cite
|
Sign up to set email alerts
|

Plant Selection for the Establishment of Push–Pull Strategies for Zea mays–Spodoptera frugiperda Pathosystem in Morelos, Mexico

Abstract: Regulations imposed on the use of chemical insecticides call for the development of environmental-friendly pest management strategies. One of the most effective strategies is the push–pull system, which takes advantage of the behavioral response of the insect to the integration of repellent stimuli; it expels the pest out of the main crop (push), while attracting stimuli (attractants) pull the pest to an alternative crop or trap (pull). The objective of this study was to design a push–pull system to control Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…In this study, the field effectiveness of the Push–Pull systems proposed by Guera et al [ 16 ] for S . frugiperda management in maize crops in the state of Morelos, Mexico, was evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the field effectiveness of the Push–Pull systems proposed by Guera et al [ 16 ] for S . frugiperda management in maize crops in the state of Morelos, Mexico, was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“… Source: Guera et al [ 16 ]; ¥ trap plants established at a distance around the main crop; * plants intercropped in the main crop. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Crotalaria plants can be used in push-pull systems, as in the study conducted by Guera et al (2020), who associated C. juncea with corn. As a result, the authors observed that when in intercrop, C. juncea made corn less attractive to fall S. frugiperda (Smith & Abbot, 1797), under laboratory and greenhouse conditions.…”
Section: Referencementioning
confidence: 99%
“…[13,17] Many of the most problematic agricultural pests are broadly distributed along with the crops they feed on. The fall armyworm Spodoptera frugiperda may cause severe damage to maize fields in Mexico (where it is native), as well as in Kenya or Uganda, [40,41] and has spread across the African continent from north to south, and east to west; [42] as has the Asian spotted stemborer Chilo partellus. [43] Cotesia sesamiae wasps, which parasitize several stemborer species, are reported to have similarly wide distributions as their hosts across sub-Saharan Africa.…”
Section: Spatial Relationships In Push-pull Systemsmentioning
confidence: 99%